Deux révoltées qui tiennent à se faire entendre: Chahdortt Djavann et Djemila Benhabib. Issue 2 (July 2015) - Spencer, Samia I.
Abstract : Chahdortt Djavann, born in Iran, has lived in France since 1993, and Djemila Benhabib, born to an Algerian father and a Cypriot-Greek mother, spent three years in Paris, before settling in Québec in 1997. Despite their different language and cultural backgrounds, both grew up in Muslim families, during an important juncture of their nations' histories, having witnessed the transformation of their religion before and after the advent of political Islam. As writers, they deal bodly with controversial social and political issues throughout the world. Their perspectives offer invaluable insight into recent developments on both sides of the Atlantic.